Combining ability Analyses for Protein Content and Maturity Traits in Spring Wheat (Triticum aestivum) - M.A. Khan, Kamaluddin*, R.M. Singh and (Journal of Phytology, 2011)
Combining ability analyses were carried out for protein content, days to 50% heading, days to 50% heading in growing0 days (GDD), days to 50% flowering, days to 50% flowering in growing0 days (GDD), days to 50% physiological maturity, days to 50% physiological maturity in growing0 days (GDD), No. of grains/ spike, 1000 grain weight and grain yield/ plant in spring wheat. Additive as well as dominance gene action was responsible for expression of these traits. Most of the genotypes were found to be superior general combiners for protein content and other traits studied. Like wise, crosses involving diverse parents showed significant SCA effects for protein content and other traits. To ensure further increase in protein content with optimum maturity duration, combinations of desirable component traits is advocated. Biparental and/or diallel selective mating design would be useful methods for further improvement of protein content with optimum level of maturity time and grain yield in spring wheat.